Self-Assembled Minimalist Multifunctional Theranostic Nanoplatform for Magnetic Resonance Imaging-Guided Tumor Photodynamic Therapy - Zhang, Han; Liu, Kai; Li, Shukun; Xin, Xia; Yuan, Shiling; Ma, Guanghui; Yan, Xuehai (ACS nano, 2018)
Minimalist multifunctional platforms for delivering diagnostic and therapeutic agents effectively and safely into tumor sites are highly desired in nanomedicine. Herein, we describe the fabrication of a supramolecular nanoplatform via the amphiphilic amino acid (9-fluorenylmethyloxycarbonyl-l-leucine, Fmoc-l-L)-modulated self-assembly of a magnetic resonance imaging (MRI) contrast agent (ionic manganese, Mn2+) and photosensitive drug (chlorin e6, Ce6). Coordination drives the coassembly of Fmoc-l-L and Mn2+ to generate a nanoscale supramolecular network to adaptively encapsulate Ce6. The obtained biometal–organic nanoparticles exhibit a high drug loading capability, inherent good biocompatibility, robust stability, and smart disassembly in response to glutathione (GSH). The cooperative assembly of the multiple components is synchronously dynamic in nature and enables enhanced photodynamic therapy (PDT) to damage tumor cells and tissue by efficiently delivering the photosensitizer and improving the reductive tumor microenvironment via the competitive coordination of GSH with Mn2+. The antitumor effect can also be monitored and evaluated in vivo by MRI through the long-term intracellular biochelation of Mn2+. Therefore, this work presents a one-pot and robust method for the self-assembly of a multifunctional theranostic nanoplatform capable of MRI-guided PDT starting from minimalist biological building blocks.